2016
DOI: 10.1016/j.jcrc.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Health care–associated pneumonia in the intensive care unit: Guideline-concordant antibiotics and outcomes

Abstract: Purpose Recent data have not demonstrated improved outcomes when guideline-concordant (GC) antibiotics are given to patients with healthcare-associated pneumonia (HCAP). This study was designed to evaluate the relationship between health outcomes and GC therapy in patients admitted to an ICU with HCAP. Materials and Methods We performed a population-based cohort study of patients admitted to >150 hospitals in the U.S. Veterans Health Administration system to compare baseline characteristics, bacterial pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Since then, many studies have demonstrated that the factors used to define HCAP do not predict high prevalence of antibiotic-resistant pathogens in most settings. Moreover, a significant increased use of broad-spectrum antibiotics (especially vancomycin and antipseudomonal β-lactams) has resulted, without any apparent improvement in patient outcomes ( 124 133 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…Since then, many studies have demonstrated that the factors used to define HCAP do not predict high prevalence of antibiotic-resistant pathogens in most settings. Moreover, a significant increased use of broad-spectrum antibiotics (especially vancomycin and antipseudomonal β-lactams) has resulted, without any apparent improvement in patient outcomes ( 124 133 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…However, this approach of ''clinical reasoning,'' even when supplemented by institution-specific algorithms developed for the prediction of infection with antibiotic-resistant bacteria, is of limited clinical utility [17]. This inaccuracy in clinical decision-making often leads to overtreatment with empiric broad-spectrum antibiotics but also the administration of IIAT [17,18]. The recent recommendation to eliminate the use of the term ''HCAP'' is in large part a response to the increasing use of empiric broadspectrum antibiotics in patients with community-onset pneumonia [10,19].…”
Section: Discussionmentioning
confidence: 99%
“…69 Concerns about adverse events and antibiotic resistance in patients who received broad spectrum antibiotic therapy were raised and an increasing body of evidence showed a greater risk of mortality in patients with HCAP risk factors who received broad-spectrum therapy relative to patients treated with standard CAP therapy. 70,71 To address these limitations of the HCAP definition, scientists developed multiple clinical prediction models attempting to identify MDR pathogens in CAP. 5,16,17,19,[72][73][74][75][76] Although these scores showed an area under the receiver operating characteristic (AUROC) curve higher than the original HCAP criteria in predicting pneumonia due to resistant pathogens, they were not designed to predict the risk of each individual MDR pathogen, such as MRSA or P. aeruginosa, with few exceptions.…”
Section: Risk Factors Associated With Resistant Gnb In Capmentioning
confidence: 99%